A rare case of death from acute hemorrhagic necrosis of the pancreas after influenza infection - Baltov, Marin; Bivolarski, Iliya; Tsranchev, Ivan; Gulinac, Milena; Dineva, Plamena; Ivanov, Georgi (Indian Journal of Case Reports, 2020)
Acute pancreatitis is an inflammatory response of the pancreas that can be caused by various conditions, including chronic alcoholism, gallstones, hypertriglyceridemia, narcotics, and tumors. Furthermore, this can be provoked by various infectious agents. Experimental studies suggest the role of influenza virus as a cause of inflammation of the pancreas. Few cases are published about H1N1 and avian influenza induced destruction of the pancreas. This case report refers to a 29-year-old man who attended an outpatient clinic, and who died suddenly at his home after acute viral infection. The forensic and histological examinations showed that death had occurred as a result of acute hemorrhagic necrosis of the pancreas caused by viral infection. The microscopical findings were hemorrhagic-necrotizing changes into the trachea, hemorrhages into the lungs and inflammatory infiltrate with lymphocytes, which features correspond to the typical changes caused by the influenza virus.